Selection of mobile network operator using Analytical Hierarchy Process (AHP) / Nida Fatihah Abdul Rahman, Sumaiyah Noorzali and Syaidatul Mardiana Omar - Nida Fatihah, Abdul Rahman; Noorzali, Sumaiyah; Omar, Syaidatul Mardiana (2018)
In Malaysia, the most well-known mobile network operator subscribed are Celcom, Maxis, Digi and U Mobile. These mobile network operators promote a variety of data package to attract user for buy. The Analytic Hierarchy Process model is used to select the multi-criteria decision-making problem in selecting the most preferred mobile network operator in the selected area, Universiti Teknologi Mara (UiTM) Negeri Sembilan. Criteria related mobile network operator were considered and questionnaires regarding selection of mobile network operator were distributed among students and staffs in three branch campuses of UiTM Negeri Sembilan, which are Seremban, Rembau and Kuala Pilah. The objective of this study is to identify the important criteria that were considered by user in choosing the best mobile network by using Analytic Hierarchy Process (AHP) and to identify the most preferred mobile network operator among user also using AHP. As the result TM and Celcom are found to be the most preferable mobile network operator among students and staffs. Network coverage becomes most important criteria in selection process followed by data package, price and value added